TEMBANG DOLANAN SEBAGAI MEDIA PENDIDIKAN KARAKTER - Sukisno Sukisno (FBS UNY, 2021)
The social phenomenon in children's tembang dolanan education is one of the educational activities that is rarely implemented and taught in public schools. Mulok (local content) does not receive enough attention from managers and educational policy makers. After policy makers and education managers know that the art of tembang has characteristics in which there are noble values, national personality values, and is beneficial to life, then the art of tembang dolanan children is included in the learning curriculum in public schools. The policy towards children's play songs as learning material in schools has been started since the birth of educational reform. Education Reform contained in the regional autonomy law. This opportunity is given to provinces and districts or cities to manage education in a decentralized manner or the handover of government power by the central government to autonomous regions based on the principle of autonomy. This definition is in accordance with Law number 23 of 2014. With the existence of decentralization, autonomy for a regional government emerged. According to Tilaar (2002: 20), decentralization of education is related to three things, namely: 1) the development of a democratic society, 2) the development of social capital and 3) an increase in competitiveness. These three things can be used as signs, references and reasons for implementing children's tembang dolanan education that are within the scope of decentralization in districts or cities. Why, in fact, cannot be implemented properly.AbstrakFenomena sosial dalam Pendidikan tembang dolanan anak merupakan salah satu aktivitas pendidikan yang semakin jarang dilaksanakan dan diajarkan di sekolah-sekolah umum. Mulok (muatan lokal) kurang mendapat perhatian dari para pengelola dan penentu kebijakan pendidikan. Setelah para penentu kebijakan dan para pengelola Pendidikan mengetahui bahwa seni tembang memiliki karakteristik yang di dalamnya terdapat nilai-nilai luhur, nila-nilai kepbribadian bangsa, dan bermanfaat bagi kehidupan, kemudian seni tembang dolanan anak dimasukkan dalam kurikulum pembelajaran di sekolah-sekolah umum.Kebijakan terhadap tembang dolanan anak sebagai materi pembelajaran di sekolah sudah diawali sejak lahirnya reformasi Pendidikan. Reformasi Pendidikan yang tertuang dalam undang-undang otonomi daerah. Peluang ini diberikan kepada wilayah daerah propinsi dan kabupaten atau kota untuk mengelola pendidikan secara desentralisasi atau penyerahan Kekuasaan Pemerintahan oleh Pemerintah Pusat kepada daerah otonom berdasarkan Asas Otonomi. Pengertian ini sesuai dengan Undang-undang nomor 23 tahun 2014. Dengan adanya desentralisasi maka muncul otonomi bagi suatu pemerintahan daerah. Menurut Tilaar (2002:20) desentralisasi pendidikan berhubungan dengan tiga hal, yaitu:1) pengembangan masyarakat demokratis, 2) pengembangan sosial kapital dan 3) peningkatan daya saing. Ketiga hal tersebut dapat digunakan sebagai rambu-rambu, acuan dan alasan pelaksanaan pendidikan tembang dolanan anak yang berada dalam lingkup desentraslisasi di kabupaten atau kota. Mengapa pada kenyataannya belum bisa dilaksanakan dengan baik.Kata Kunci : Media Pendidikan karakter melalui Tembang